The cancer cachexia syndrome – aetiopathogenesis and current knowledge - Lizak, Adam; Kałmuk, Andrzej; Huras, Barbara; Prudło, Izabela (Contemporary Oncology/Współczesna Onkologia, 2003)
Cachexia syndrome is a common complication occurring in cancer patients. Almost 45% of patients hospitalized because of cancer lose more than 10% of their initial weight, and 25% of them lose more than 20% of weight. The major symptom of cachexia in patients suffering from a malignant tumour, which is the loss of weight, is the result of systemic and topical effect of a tumour. In the course of cachexia food intake changes, and so do energy and substance substrate requirement and consumption. The pace of cachexia syndrome development varies. It depends on the kind of a tumour, its localization and the treatment undertaken. Metabolic and hormona abnormalities which occur in cachexia are parallel to starvation and/or an action of an injury to an organism. Application of an intense parenteral nutrition as the only way of dealing with cachexia does not cause any improvement in mood or regression of symptoms. Parenteral nutrition does not affect the patients’ lifetime. The current knowledge about cachexia syndrome aetiopathogenesis proves that a key role in commencing the process of metabolic abnormalities is given to cytokines, including the major cytokine TNF, tumour necrosis factor. An essential role is also played by an inflammatory state reaction transmitter as well as endogenic peptides which occur as a result of the tumour presence in the organism. The knowledge about cachexia pathomechanism and therapeutic possibilities allows implementing an adequate and interdisciplinary treatment of cachexia. The aim of such actions is to increase patients’ chances for casual treatment, and in the last phase of the disease the improvement of a life quality. The current knowledge explains the mechanism of metabolic and hormonal changes occurring in cachexia, and explains why cachexia develops in patients with certain types of tumour.